PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN STRATEGI PEMBELAJARAN SURVEY QUESTION READ REFLECT RECITE REVIEW FASE C KELAS V SDN 100/II MUARA BUNGO - Muhammad Khairul Khairul (Jurnal Dharma PGSD, 2025)
This research is motivated by the low reading comprehension skills of fifth-grade students of SDN 100/II Muara Bungo. The purpose of this study is to improve the learning process and students' reading comprehension skills by using the SQ4R learning strategy for fifth-grade students of SDN 100/II Muara Bungo. This type of research is Classroom Action Research which is carried out in 2 cycles and each cycle has 2 meetings which include planning, implementation, observation, and reflection. The research method used is Classroom Action Research (CAR). The research was carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection. The subjects of this study were 17 fifth-grade students of SDN 100/II Muara Bungo. Data collection used in this study is qualitative and quantitative data. The results of the study show that in cycles I, II, and III in this study, it can be concluded that the application of the SQ4R strategy can improve the reading comprehension skills of fifth-grade students of SDN 100/II Muara Bungo.